Pengaruh modul anemia anak dalam meningkatkan pengetahuan dan sikap kader kesehatan - Yuliantisari Retnaningsih; Nur Djanah; Sukani Sukani (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Globally it is estimated that 40% of all children aged 6-59 months are affected by anemia. Anemia is not a disease but rather a reflection of the condition of a disease or impaired body function. The real impact of nutritional anemia on the quality of human resources. Especially in children under five, children will be more susceptible to disease due to decreased immune system. The role of health cadres is needed for mothers and toddlers in the form of assistance and health education.Objectives: This research aims to determine the effect of Health Education with module of child anemia to improve the knowledge and attitudes of health cadres.Methods: Quasi i-experimental type with a pre-post test control group design. The sample were health cadres in the Dlingo II Bantul Community Health Center, 30 respondents intervention group and 30 respondents control group. The sampling technique was cluster random sampling.Results: The results of the analysis showed that after treatment there was a significant increase in knowledge and attitudes in the intervention group (p=0,000) and the control group (p=0,001). There was a significant difference between the intervention group and the control group on the variables of knowledge (p = 0,032) and attitude (p = 0,026).Conclusion: Health education through modules is more effective than using leaflets in improving the knowledge and attitudes of cadres about anemia in children. KeywordsModule, Anemia, Health Cadres, Knowledge, Attitude